Preferential Trade Agreements and Tax Competition for Foreign Direct Investment - Horst Raff (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper examines how free-trade agreements and customs unions affect the location of foreign direct investment (FDI) and social welfare, taking into account that governments may adjust taxes and external tariffs to compete for FDI. Conditions are identified under which a free-trade agreement leads to FDI and under which this improves welfare. The welfare effect is shown to depend on the relative size of efficiency gains in production and government revenue losses due to tax competition. A free-trade agreement may fail to induce welfare-improving FDI, creating a role for a customs union.
Keywords: 330; preferential trade agreements; tax competition; multinational enterprises